Cutaneous metastases from solid neoplasms - Literature review - Bruno de Castro e Souza; Denis Miyashiro; Marcella Soares Pincelli; José Antonio Sanches (Sociedade Brasileira de Dermatologia, 2023)
Abstract Cutaneous metastases from solid tumors are uncommon events in clinical practice. Most of the time, the patient already has the diagnosis of a malignant neoplasm when the cutaneous metastasis is detected. However, in up to one-third of cases, cutaneous metastasis is identified before the primary tumor. Therefore, its identification may be essential for starting treatment, although it is usually indicative of poor prognosis. The diagnosis will depend on clinical, histopathological, and immunohistochemical analysis. Sometimes the identification of the primary site is difficult; however, a thorough analysis using imaging tests and constant surveillance is important.